2021
DOI: 10.1088/1755-1315/919/1/012057
|View full text |Cite
|
Sign up to set email alerts
|

The replacement of fish meal with fermented Moringa leaves meal and its effect on the immune response of red tilapia (Oreochromis sp.)

Abstract: Moringa (Moringa oleifera) has frequently been studied as an alternative and promising protein source in fish feed. Moringa leaves is among the potential and affordable plant-based protein source ingredient, as it protein, vitamin, beta-carotene, and various kind of minerals. Flavonoid, saponin, vitamin and alkaloids reportedly exhibit immune-stimulating activity which increase immune response. This study aims to evaluate the replacement of fish meal with fermented Moringa leaves meal in feed on the immune res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The water extract of some herbs has been proven to increase the immune response of whiteleg shrimp [ 28 , 29 , 39 , 40 ]. Moringa herb has antitumor, antioxidant, anticancer, antistress, immunostimulatory effects in gilthead seabream ( Sparus aurata ) and nile tilapia [ 41 , 42 , 43 , 44 , 45 ], because of its phytochemicals, such as phenolic acid, flavonoids, carotenoids, alkaloids, tannin, lectin, and terpenoids [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The water extract of some herbs has been proven to increase the immune response of whiteleg shrimp [ 28 , 29 , 39 , 40 ]. Moringa herb has antitumor, antioxidant, anticancer, antistress, immunostimulatory effects in gilthead seabream ( Sparus aurata ) and nile tilapia [ 41 , 42 , 43 , 44 , 45 ], because of its phytochemicals, such as phenolic acid, flavonoids, carotenoids, alkaloids, tannin, lectin, and terpenoids [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolyzed purslane through enzymatic reaction resulted in a reduction of ash content from 10.19% to 8.04%. The ash content within the hydrolyzed purslane exhibited a notable , 03029 (2024) BIO Web of Conferences ICFAES 2023 https://doi.org/10.1051/bioconf/20248703029 87 decrease in comparison to that of Moringa leaves meal (9.70%) and fermented Moringa leaves meal (14.05%) [39].…”
Section: Resultsmentioning
confidence: 99%
“…Similar results of protein variation in red tilapia ( Oreochromis sp.) fed with fermented moringa leaves based feed reported by Helmiati et al [ 47 ]. In addition, Adeshina et al [ 14 ] reported the similar result where moringa based feed showed a higher protein efficiency ratio than the control.…”
Section: Discussionmentioning
confidence: 99%